1977
DOI: 10.1021/jm00222a008
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic agents. 1. N-Protected vinyl, 1,2-dihaloethyl, and cyanomethyl esters of phenylalanine

Abstract: A series of N-protected vinyl, 1,2-dihaloethyl, and cyanomethyl esters of phenylalanine was synthesized and these compounds were evaluated for antitumor activity against the growth of Ehrlich ascites carcinoma in CF1 male mice (33 mg/kg/day), Walker 256 carcinosarcoma in Sprague-Dawley male rats (2.5 mg/kg/day), and P388 lymphocytic leukemia in DBA/2 mice (20 mg/kg/day). Structure-activity relationships were evaluated and acute toxicity studies (LD50 determinations) in male CF1 mice were also carried out on se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…N-protected amino acid O-vinyl ester (AAVE) monomers were synthesized by Pd-catalyzed transvinylation of N-(tert-butoxycarbonyl) (Boc) protected amino acids with vinyl acetate (VAc). These vinyl ester monomers have been previously synthesized from either Boc or N-carboxybenzyl (CBz) protected amino acids and VAc with KOH and either PdCl 2 , 44 Pd(OAc) 2 , 45,46 or Na 2 PdCl 4 42,47 as catalysts. We found that these reported procedures typically produced low yields of the desired monomers (#30%), likely as a result of decomposition of the active Pd(II) catalysts to inactive Pd(0) black.…”
Section: Resultsmentioning
confidence: 99%
“…N-protected amino acid O-vinyl ester (AAVE) monomers were synthesized by Pd-catalyzed transvinylation of N-(tert-butoxycarbonyl) (Boc) protected amino acids with vinyl acetate (VAc). These vinyl ester monomers have been previously synthesized from either Boc or N-carboxybenzyl (CBz) protected amino acids and VAc with KOH and either PdCl 2 , 44 Pd(OAc) 2 , 45,46 or Na 2 PdCl 4 42,47 as catalysts. We found that these reported procedures typically produced low yields of the desired monomers (#30%), likely as a result of decomposition of the active Pd(II) catalysts to inactive Pd(0) black.…”
Section: Resultsmentioning
confidence: 99%
“…Condition optimization for substitution reaction Usually, amino acid propargyl esters were synthesized via condensation using N-protected amino acid and propargyl alcohol as materials, and the reported synthetic methods have many drawbacks, such as higher reaction temperature, multi-step reaction processes, more expensive reagents, longer reaction times, especially the tiresome condensing agents for their difficulty in the thorough separation from the products [32][33][34][35][36]. There are only a few reports on the synthesis of amino acid propargyl esters using N-protected amino acid and propargyl bromide as materials [37].…”
Section: Resultsmentioning
confidence: 99%
“…Carbobenzoxy [cbz]phenylalanine vinyl esters and 1,2-dibromoethyl esters have previously been shown to be potent anti-neoplastic and antiinflammatory agents in rodents (Loeffler et al, 1977a). These studies were extended to other amino acids, e.g.…”
Section: Introductionmentioning
confidence: 99%